OUTCOMES OF TRANSFORAMINAL LUMBAR INTERBODY FUSION AND POSTERIOR LUMBAR INTERBODY FUSION IN MANAGING SINGLE-LEVEL LUMBAR SPONDYLOLISTHESIS - Khattak, Haider Ali; Nasim Gul,; Adnan Khaliq,; Mian Iftikhar ul Haq,; Shahid Nawaz,; Khan, Shahbaz Ali (Journal of Ayub Medical College Abbottabad, 2024)
Background: There is significant discussion over the most effective surgical approach for treating lumbar spondylolisthesis, despite the recommendation of a number of surgical approaches. The aim of this study was to explore the Outcomes of transforaminal lumbar interbody fusion and posterior lumbar interbody fusion in managing single-level lumbar spondylolisthesis. Methods: The current study was conducted at the department of orthopedic and neurosurgery from January 2022 to February 2023 after taking approval from the ethical committee of the institute. Those individuals who had experienced a single-level condition with a low-grade categorization (grades I or II) in the Meyerding grading system were included in the study. A total of 52 patients were enrolled in this study and were divided in to group A and B. 26 received PLIF, and were placed in group A while 26 had done TLIF and were placed in group B. The two groups' mean operating times, blood loss, VAS scores for back and leg discomfort, and complications were compared. SPSS 24 was used for data analysis. While frequency and percentages were used to analyze categorical data, mean and standard deviation were used for analyzing numerical statistics. To compare numerical values between the two groups, the Independent Samples T-test was used, with the p value significant at < 0.05. Results: A total of 52 individuals were enrolled in this investigation, distributed evenly into two groups. The mean age of the participants was 35.14±7.76 years. Out of 52 patients male were 30(57.6% and 22(42.30) were females. Patients in group B underwent TLIF while patients in group A got PLIF. With respect to the results for the two groups, individuals in the group A had mean operative time 126.44±12.03 minutes and Group B had a considerably shorter duration of 113.32±8.48 minutes (P < 0.05). In group A, the average blood loss was 440±76.33 cm3 but Group B experienced a much lower value of 371.40±39.2 cm³ (P < 0.05). Concerning postoperative VAS leg pain, there was no difference between the two groups (P > 0.05) while group B experienced considerably less postoperative pain in the back on the VAS than group A did (P < 0.05). Dural tear was noted in 4 participants in group A, while 2 in group B. 3 patients in group A experienced a neurologic impairment, but in group b there was no neurologic deficit noted. 3 individuals in group A experienced wound infections, whereas none of the patients in group B did. Conclusion: Based on our research, TLIF is better than PLIF in terms of functional result and rate of complications in patients with grade I/II single-level lumbar spondylolisthesis.